Examining computationally the structural, elastic, optical, and electronic properties of CaQCl3 (Q = Li and K) chloroperovskites using DFT framework. Issue 50 (11th November 2022) - Husain, Mudasser; Rahman, Nasir; Albalawi, Hind; Ezzine, Safa; Amami, Mongi; Zaman, Tahir; Rehman, Altaf Ur; Sohail, Mohammad; Khan, Rajwali; Khan, Abid Ali; Tahir,; Khan, Aurangzeb
Abstract : This study presents the investigations of structural, elastic, optical, and electronic properties of CaQCl3 (Q = Li and K) chloroperovskites for the first time using the DFT framework. Abstract : This study presents the investigations of structural, elastic, optical, and electronic properties of CaQCl3 (Q = Li and K) chloroperovskites for the first time using the DFT framework. The WIEN2K and IRelast packages are used in which the exchange–correlation potential of the modified Becke–Johnson potential (TB-mBJ) is used for obtaining better results. The optimized crystal structural parameters comprising the lattice constant, optimum volume, ground state energy, bulk modulus, and the pressure derivative of bulk modulus are computed by fitting the primitive unit cell energy versus primitive unit cell volume using the Birch–Murnaghan equation of state. The elastic properties which consist of cubic elastic constants, Poisson's ratio, elastic moduli, anisotropy factor, and the Pugh ratio are computed using the very precise IRelast package incorporated inside WIEN2K. The electronic properties are analyzed from the computation of electronic bands structure and density of states (DOS), and it is concluded that an indirect band gap of 4.6 eV exists for CaLiCl3 and a direct band gap of 3.3 eV for CaKCl3 which confirms that CaLiCl3 is an insulator while CaKCl3 is a wide band gap semiconductor. The analysis of DOS shows that the greater contribution to the conduction band (CB) occurs because of the "Ca" element whereas in the valence band the major contribution is from the "Cl" element. The spectral curves of various parameters of optical properties from 0 eV up to 42 eV incident photon energies are observed and it is found that the CaQCl3 (Q = Li and K) chloroperovskites are optically active having a high absorption coefficient, optical conductivity, optical reflectivity, and energy loss function from 25 eV to 35 eV incident photon energies. The applications of these materials can be deemed to alter or control electromagnetic radiation in the ultraviolet (UV) spectral regions. In summary, the results for selected CaQCl3 (Q = Li and K) chloroperovskites depict that these are important compounds and can be used as scintillators, and energy storage devices, and in many modern electronic gadgets.